Using Deliberative Techniques to Engage the Community in Policy Development: A Case Study - Gregory, J.; Hartz-Karp, Janette; Watson, R. (BioMed Central, 2008)
Background: This paper examines work in deliberative approaches to community enagement used in Western Australia by the Department of Planning and Infrastructure and other planning and infrastructure agencies between 2001 and 2005, and considers whether the techniques could be applied to the development of health policy in Australia. Results: Deliberative processes were used in WA to address specific planning and infrastructure problems. Using deliberative techniques, community participants contributed to joint decision making and policy development. Outcomes from deliberative processes were seriously considered by the Minister and used to influence policy decisions. In many cases, the recommendations generated through deliberative processes were fully adopted by the Minister. Conclusion: The experiences in WA demonstrate that deliberative engagement processes can be successfully implemented by government and can be used to guide policy. The techniques can be adapted to suit the context and issues experienced by a portfolio, and the skills required to conduct deliberative processes can be fostered amongst the portfolio's staff. Health policy makers may be able to learn from the experiences in WA, and adopt approaches to community engagement that allow for informed deliberation and debate in the community about the future of Australia's health system.